1983
DOI: 10.1007/bf01002987
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tissue preparation methods and paired immunofluorescence staining for immunocytochemistry of lymphomas

Abstract: Eight cross-linking fixatives were tested for preservation of extracellular or intracellular IgG, IgA, IgM, IgD, kappa and lambda light chains, J chain and secretory component. Most of the selected fixatives have been used in recent immunohistochemical studies of lymphoproliferative processes and comprised routine formalin, glutaraldehyde(1%)-formalin, Baker's formalin-calcium, formalin-sublimate, acetic acid(2%)-formalin-saline, Bouin's fluid, Susa fixative, and carbodiimide. The results obtained in artificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…In some cases extracellular staining was observed both in tubules and between cells. Staining of the intracytoplasmic vacuoles was also considered extracellular, as electron microscopy has shown that the surface of the inner membrane of the vacuole has features typical of the exterior surface of the cell membranes (Battifora, 1975 (Brandtzaeg & Rognum, 1982). The change in the immunohistochemical staining pattern from extracellular in normal and benign breast tissue to mixed with varying amounts of intracellular positivity in malignant breast tissue has been observed using other antibodies Foster et al, 1982) and lectins (Franklin, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases extracellular staining was observed both in tubules and between cells. Staining of the intracytoplasmic vacuoles was also considered extracellular, as electron microscopy has shown that the surface of the inner membrane of the vacuole has features typical of the exterior surface of the cell membranes (Battifora, 1975 (Brandtzaeg & Rognum, 1982). The change in the immunohistochemical staining pattern from extracellular in normal and benign breast tissue to mixed with varying amounts of intracellular positivity in malignant breast tissue has been observed using other antibodies Foster et al, 1982) and lectins (Franklin, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In pathological conditions, such as inflammation, dysplasia and carcinoma, the epithelium may express varying amounts of these antigens (Rognum et al, 1983(Rognum et al, , 1987Ruiz-Cabello et al, 1988). The presence of HLA-DR on the surface membrane of the neoplastic cells is a prerequisite for recognition by activated CD4+ T cells, and it has been shown that the growth of colorectal cancer cells expressing class II following y-interferon treatment is inhibited by activated CD4+ T-helper cells , indicating a direct cytotoxic effect (Gjertsen et al, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…HLA-DR immunohistochemistry A murine monoclonal antibody to a non-polymorphic human HLA-DR antigen, clone L234 (IgG2a, Beckton Dickinson, Mountain View, CA, USA) was applied (1:20 for 20 h) in an indirect three-step immunofluorescence method (Brandtzaeg and Rognum, 1983), including affinity purified biotinylated horse anti-mouse IgG (0.05 g IgGI-1, 3 h) and fluorescein isothiocyanate (FITC)-labelled avidin (0.05 g 1-', 30 min), both purchased from Vector Laboratories (Burlingame, CA, USA).…”
Section: Controlsmentioning
confidence: 99%
“…One section from each series was stained by a trichrome routine method (HAS) containing haematoxylin, azofloxin, and saffron (Stave & Brandtzaeg, 1977 (Rognum et al, 1980). The red signal from this conjugate was enhanced by combining the FITC-labelled avidin with a TRITClabelled swine anti-rabbit IgG (Brandtzaeg & Rognum, 1983 (Rognum et al, 1980). Both the tumour and the adjacent transitional mucosa were evaluated.…”
Section: Immunohistochemistrymentioning
confidence: 99%